Pola Rima Syi'iran dalam Naskah di Tatar Sunda dan Hubungannya dengan Pola Rima Syair Arab - Titin Nurhayati Ma'mun (Masyarakat Pernaskahan Nusantara, 2011)
Syi'iran is a familiar tradition in the Islamic boarding school (pesantren) world, particularly in Tatar Sunda. Besides being used to convey thoughts that generally take the form of invitations/exhortations, syi'iran is also utilized as a medium to impart Islamic teachings, specifically to santri (students) and generally to the community surrounding the pesantren. The use of syi'iran as an educational medium is viewed as highly effective because it is easier to remember and does not burden santri (or the community) with formal situations and learning patterns typical of general educational processes. Due to being sung or listened to frequently, syi'iran can naturally be memorized by heart without compulsion, which positively impacts the educational process around the pesantren. Through syi'iran, santri and the general public are expected to be awakened in their consciousness and possess the desire to follow the advice and religious teachings chanted through it. Given how deeply rooted the syi'iran tradition has been in Tatar Sunda over a long period, besides still being enjoyed via loudspeakers during religious recitations today, it is also proven by the presence of syi'ir notes found in classical manuscripts. The easiest aspect to recognize in manuscript syi'iran is the repetition of final sounds that form a musicality or orchestration, making syi'iran melodious when read. The habit of chanting Arabic poetry—whether through the tradition of reading the Barzanji, Shalawat, or poetic excerpts in Kitab Kuning—more or less, consciously or unconsciously, influences the rhyming patterns of syi'iran composed by local communities. This brings about several correspondences in rhyming patterns between syi'iran and Arabic poetry. The rhyming patterns of syi'iran in Sundanese manuscripts and their relation to the rhyming patterns of Arabic poetry discussed in this paper are expected to assist the text edition process in philological research, particularly for texts written in the form of syi'iran. === Syi'iran merupakan sebuah tradisi yang tidak asing lagi di dunia pesantren, khususnya yang terdapat di Tatar Sunda. Selain dipergunakan untuk menyampaikan buah pikiran yang umumnya berupa ajakan, syi'iran di gunakan pula sebagai media untuk menyampaikan ajaran agama Islam, khususnya kepada para santri dan umumnya kepada masyarakat di sekitar pesantren. Penggunaan syi'iran sebagai media pendidikan dipandang sangat efektif karena lebih mudah diingat dan tidak membebani santri (masyarakat) dengan situasi dan pola formal sebagaimana proses pembelajaran pada umumnya. Karena seringnya dinyanyikan atau diperdengarkan, syi'iran dengan sendirinya dapat dihafalkan di luar kepala tanpa keterpaksaan, hal ini tentu membawa dampak bagi proses pendidikan di sekitar pesantren. Melalui syi'iran, diharapkan para santri serta masyarakat umum tergugah kesadarannya dan memiliki keinginan untuk mengikuti nasihat serta ajaran agama yang disenandungkan melalui syi'iran tersebut. Demikian mengakarnya tradisi syi'iran yang telah berlangsung sejak lama di Tatar Sunda, selain saat ini masih dapat dinikmati melalui pengeras suara di pengajian-pengajian juga dapat dibuktikan dengan adanya catatan-catatan syi'ir yang terdapat pada naskah klasik. Hal yang paling mudah diketahui dari syi'iran pada naskah adalah adanya pengulangan bunyi akhir yang membentuk musikalitas atau orkestrasi sehingga membuat syi'iran menjadi merdu jika dibaca. Adanya kebiasaan melantunkan syair-syair Arab baik melalui tradisi pembacaan Barzanji, Shalawat, atau kutipan-kutipan syair pada Kitab Kuning sedikit banyak, baik disadari ataupun tidak, mempengaruhi pola rima syi'iran yang digubah oleh masyarakat lokal. Hal ini memunculkan sejumlah kesesuaian pola rima antara syi'iran dan sya'ir Arab. Pola rima syi'iran dalam naskah Sunda dan hubungannya dengan pola rima syair Arab yang dibahas dalam makalah ini diharapkan dapat membantu proses edisi teks dalam penelitian filologi, khususnya untuk teks yang berbentuk syi'iran.